Pengaruh Mikroba Antagonis dari Buah Jeruk terhadap Pertumbuhan Jamur Patogen Geotrichum sp. Penyebab Penyakit Busuk Asam pada Buah Lemon (Citrus limon L. Burm) - Bawantari, Ni Komang Sri; Suprapta, Dewa Ngurah; Wirya, Gusti Ngurah Alit Susanta (Agrotrop : Journal on Agriculture Science, 2025)
Effect of Antagonistic Microbes from Citrus Fruit on the Growth of the Pathogenic Fungus Geotrichum sp. the Cause of Sour Rot Disease in Lemon Fruit ( Citrus limon L. Burm). The pathogenic fungus Geotrichum citri-aurantii is a yeast from the Saccharomycetes class which can infect several types of agricultural plants. This fungus is very detrimental to the productivity of lemons ( Citrus limon L. Burn). The use of biological agents is an alternative method recommended for controlling plant diseases. Disease control using biological agents is selective and good for the ecosystem. The aim of this research was to determine the effect of antagonistic microbes from citrus fruit on the growth of the pathogenic fungus G. citri-aurantii which causes sour rot disease on lemons. Research was carried out in vitro and in vivo in the laboratory as well as molecular identification at Sience Genetics. The results of the research show that the fungal pathogen that infects lemon fruit and causes sour rot disease is the fungus G. citri-aurantii . The results of molecular identification of antagonistic microbial isolates from Lumajang oranges (Lu1) showed that the microbes were Bacillus velezensis . Antagonistic microbial treatment significantly (P<0.05) inhibited the growth of G. citri- aurantii fungal colonies on potato dextrose agar (PDA) media. Treatment with B . velezensis Lu1 was able to inhibit the growth of the fungus G. citri-aurantii with an inhibitory percentage of 71.20% when compared with the control when observed 7 days after inoculation. Treatment of B. velezensis Lu1 affected the biomass of the fungus G. citri-aurantii . In this study, treatment with filtrate of B. velezensis isolate Lu1 at a concentration of 40% was able to suppress the growth of G. citri-aurantii with an inhibitory percentage of 50.89% when observed 7 days after inoculation. Treatment with inoculation of B. velezensis Lu1 suspension before treatment of suspension of G. citri- aurantii in vivo on lemon fruit resuklted in an inhibitory activity of 45.27%. Further research is needed to determine the secondary metabolite compounds produced by B. velezensis Lu1 using the GC-MS method.